Functional characterization of the neuron‐restrictive silencer element in the human tryptophan hydroxylase 2 gene expression. Issue 6 (13th June 2017) - Nawa, Yukino; Kaneko, Hanae; Oda, Masayuki; Tsubonoya, Masaaki; Hiroi, Tomoko; Gentile, Maria Teresa; Colucci‐D'Amato, Luca; Takahashi, Ryoya; Matsui, Hiroaki
Abstract: Tryptophan hydroxylase 2 (TPH2) is the key enzyme in the synthesis of neuronal serotonin. Although previous studies suggest that TPH2 neuron‐restrictive silencer element (NRSE) functions as a negative regulator dependent on neuron‐restrictive silencer factor (NRSF) activity, the underlying mechanisms are yet to be fully elucidated. Here, we show a detailed analysis of the NRSE‐mediated repression of the human TPH2 (hTPH2) promoter activity in RN46A cells, a cell line derived from rat raphe neurons. Quantitative real‐time RT‐PCR analysis revealed the expression of serotonergic marker genes ( Mash1, Nkx2.2, Gata2, Gata3, Lmx1b, Pet‐1, 5‐Htt, and Vmat2 ) and Nrsf gene in RN46A cells. Tph1 mRNA is the prevalent form expressed in RN46A cells; Tph2 mRNA is also expressed but at a lower level. Electrophoretic mobility shift assays and reporter assays showed that hTPH2 NRSE is necessary for the efficient DNA binding of NRSF and for the NRSF‐dependent repression of the hTPH2 promoter activity. The hTPH2 promoter activity was increased by knockdown of NRSF, or over‐expression of the engineered NRSF (a dominant‐negative mutant or a DNA‐binding domain and activation domain fusion protein). MS‐275, a class I histone deacetylase (HDAC) inhibitor, was found to be more potent than MC‐1568, a class II HDAC inhibitor, in enhancing the hTPH2 promoter activity. Furthermore, treatment with the ubiquitin‐specific protease 7 deubiquitinase inhibitors, P‐22077 or HBX 41108, increased the hTPH2 promoter activity. Collectively, our data demonstrate that the hTPH2 NRSE‐mediated promoter repression via NRSF involves class I HDACs and is modulated by the ubiquitin‐specific protease 7‐mediated deubiquitination and stabilization of NRSF. Abstract : The human tryptophan hydroxylase 2 (hTPH2) NRSE (neuron‐restrictive silencer element) is supposed to function as a negative regulator depending on NRSF (neuron‐restrictive silencer factor) activity. We propose a model in which the hTPH2 NRSE‐mediated promoter repression via NRSF involves a class I HDACs (histone deacetylases) and is critically modulated by the ubiquitin‐specific protease 7 (USP‐7) – induced deubiquitination and stabilization of NRSF.